A “Stem Cell in Cancer” special issue in Translational Cancer Research - Zhong, Nancy Q.; Shen, Min (Chinese Journal of Cancer Research; Vol 25, No 6 (December 26, 2013): Chinese Journal of Cancer Research, 2013)
It is well-known that “somatic stem cells (SSCs) play a very important role in the maintenance of normal tissue homeostasis by replenishing dying cells and regenerating damaged tissues for the entire lifespan of an organism.” On the other hand, “because SSCs can self-renew, they are long lived cells that represent ideal cellular targets for acquisition of multiple mutations which may transform SSCs to cancer stem cells (CSCs) to cause malignancies. Failure to eradicate CSCs causes tumor recurrence after cancer treatment” (1).